What does it take to develop an effective climate change curriculum? - Eilam, Efrat (Frontiers in Education, 2025)
The present conceptual paper addresses the question: What does it take to develop an effective climate change (CC) curriculum? Three different lenses are applied in developing a comprehensive critical analysis of CC curriculum development. The first lens consists of examining current literary approaches for addressing CC curriculum development. The second lens takes an empirical approach by examining CC inclusion in two exemplary curricula, the Next Generation Science Standards (NGSS), and the State of New Jersey Student Learning Standards (NJSLS), United States of America (USA). The third lens focuses on discussing critical gaps revealed in the analysis. These include CC inclusion through a cross-curricular approach unproblematized; key socio-economic-political concepts underpinning CC not articulated; lack of thematic organization; the importance of non-linear CC thematic organization; terminological consistency; insufficient consideration given for learning progression; and disaster risk reduction—a neglected theme. The paper concludes with a set of recommendations for CC curriculum development and proposes a definition for effective CC curriculum. Overall, this analysis advances the field by identifying conceptual obstacles in existing curricula and proposing a coherent framework for more effective CC curriculum design.